2013
DOI: 10.3109/01480545.2013.834348
|View full text |Cite
|
Sign up to set email alerts
|

Changes in behavior and hematological parameters of freshwater African catfishClarias gariepinus(Burchell 1822) following sublethal exposure to chloramphenicol

Abstract: The present study was aimed at evaluating the effects of different concentrations of the most commonly used fish antimicrobial drug, chloramphenicol (CAP), on the behavior and hematological parameters of Clarias gariepinus. Fish specimens were exposed to three (2.5, 5.0 and 10.0 mg L(-1)) sublethal concentrations of CAP and a control. Abnormal behavioral changes were observed in fish exposed to higher concentration of CAP. Blood erythrocytes were sampled on days 1, 5, 10 and 15 postexposure to evaluate hematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
7
24
0
1
Order By: Relevance
“…The present study indicates that fenthion has no significant effect on eosinophils and basophils. Similar to the present findings, no significant differences in these leukocyte differentials have been reported in fish exposed to various concentrations of toxicants (Mohammad et al 2012;Roy and Nath 2012;Nwani et al 2014). After the 7-d recovery period, Hb values were restored to physiological levels except at the 8.0-mg/L concentration.…”
Section: Discussionsupporting
confidence: 89%
“…The present study indicates that fenthion has no significant effect on eosinophils and basophils. Similar to the present findings, no significant differences in these leukocyte differentials have been reported in fish exposed to various concentrations of toxicants (Mohammad et al 2012;Roy and Nath 2012;Nwani et al 2014). After the 7-d recovery period, Hb values were restored to physiological levels except at the 8.0-mg/L concentration.…”
Section: Discussionsupporting
confidence: 89%
“…Hematological parameters are important in evaluating the harmful effects of pharmaceuticals in fish (Kreutzmann 1977;Nwani et al 2014aNwani et al , 2014b. In our study, RBC counts, Hb, PCV, MCV, and MCHC were appreciably reduced at all concentrations of ABZ.…”
Section: Discussionsupporting
confidence: 46%
“…In rats Rattus novergicus, ABZ has been reported to be toxic and to modulate hematological and biochemical functions (Abd El-Rahman et al 1999;Arise and Malomo 2009;Wojtkowiak-Giera et al 2012). Hematological parameters such as red blood cells (RBCs), hemoglobin (Hb), white blood cells (WBCs), and packed cell volume (PCV) and blood indices including mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) have been used as pathophysiological indicators of the overall health condition of vertebrates, particularly fish (Nwani et al 2014a) Pharmaceuticals have been reported to cause oxidative damage in animals by producing reactive oxygen species (ROS; Abd El-Rahman et al 1999;Locatelli et al 2004;Für et al 2012). Reactive oxygen species may also cause damage to all major classes of biological macromolecules, leading to protein oxidation, lipid peroxidation, depolymerization of polysaccharides, and cellular and DNA damage.…”
mentioning
confidence: 99%
“…These characteristics have provided reliable information on metabolic disorders, chronic stress status and health status before and after clinical examination of specimens (Bahmani et al, 2001). In this study, a significant increase in WBC of the fish exposed to the chemicals could be as a result of an immune system response to the toxic effect of the chemicals as WBCs are involved in immune function regulation in many organisms (Nwani et al 2013). Saravanan et al (2012) reported a significant increase in WBC in Cirrhinusm rigala exposed to various concentrations of ibuprofen drug.…”
Section: Haematological Parameters Of Clarias Gariepinus Fingerlingsmentioning
confidence: 68%